Morphophysiological and Histopathological Effects of Ammonium Sulfate Fertilizer on Aporrectodea trapezoides (Dugès, 1828) Earthworm - Khaoula Aouaichia; Nedjoud Grara; Kamel Eddine Bazri; Edison Barbieri; Nedjma Mamine; Hadia Hemmami; Anna Capaldo; Luigi Rosati; Stefano Bellucci (Life)
The present study used the adult earthworm Aporrectodea trapezoides as a bioindicator species to look into the possible dangers of ammonium sulfate (AS) fertilizer. Two complementary toxicity tests were conducted to determine the LC50values, growth rate inhibition, morphological alterations, and histopathological texture of worms. The lethality test included four increasing concentrations of AS fertilizer (ranging from 2500 to 7500 mg/kg of dry soil weight (d.w.)), while sub-lethal concentrations were based on 10%, 30%, 40%, and 50% of the 14-day median lethal concentration (LC50), with a control group included for both tests. The LC(50) values for AS fertilizer were significantly higher at 7 days (4831.13 mg/kg d.w.) than at 14 days (2698.67 mg/kg d.w.) of exposure. Notably, earthworms exhibited significant growth rate inhibition under exposure to various concentrations and time durations (14/28 exposure days). Morphological alterations such as clitellar swelling, bloody lesions, whole body coiling and constriction, body strangulation, and fragmentation were accentuated steadily, with higher concentrations. Histopathological manifestations included severe injuries to the circular and longitudinal muscular layers, vacuolation, muscle layer atrophy, degradation of the chloragogenous tissue in the intestine, collapsed digestive epithelium of the pharynx with weak reserve inclusion, and fibrosis of blood vessels. These effects were primarily influenced by increasing concentrations of fertilizer and time exposure. The study highlights the strong relationship between concentration and exposure time responses and underscores the potential of A. trapezoides earthworms as valuable biological control agents against acidic ammonium sulfate fertilizer. Importantly, this research contributes to the use of such biomarkers in evaluating soil toxicity and the biological control of environmental risk assessment associated with chemical fertilizers.